Nurses' knowledge and practice regarding prevention of surgical site infection (SSI) in Hospital Universiti Sains Malaysia (USM) - Apandi, Nurul Eiman Danisyah Aktar (2020)
Surgical site infection is an infection that occur 30 days after surgery and cause many effects such as increasing risk of death, increasing hospital stay and financial constraints for patient and health care system. A cross sectional study has been conducted to determine nurses’ knowledge and practice regarding prevention of SSI in Hospital USM. This study also examined the difference of knowledge and practice between general surgery and orthopaedic nurses. Pearson Chi-square was used to determine the association between clinical working experience with knowledge and practice towards prevention of SSI. A total of 66 nurses, 34 nurses were from surgical and 32 nurses from orthopaedic wards were recruited through proportional sampling. Data were collected September 2019 until June 2020 using self-administered questionnaires and analysed using SPSS version 26.0 for Window. Ethical approval was obtained from Human Research Ethics Committee (HREC), Universiti Sains Malaysia. The mean age of the participants was 31 years old. The results revealed staff nurses were having poor knowledge level (M=16.18, SD= 2.745) regarding prevention of SSI. Meanwhile for level of practice, nurses were found to be having good practice towards prevention of SSI (M=67.82, SD=6.44). There was no significant difference in knowledge between general surgery and orthopaedic nurses (p=0.467). While, there was significant difference in practice between general surgery and orthopaedic nurses (p=0.013). There was no association to be found between clinical working experience with knowledge (p=0.834) and practice (p=0.197) regarding prevention of SSI. It showed that nurses need more exposure towards SSI and its prevention for them to identify, assess and implementing the correct practice. As a conclusion, it is shown that knowledge and practice towards SSI is important as the results shows that nurses in Hospital USM had insufficient knowledge. A workshop or course training should be implemented to enhance their knowledge.